Relationship between Maxillary Molar Root Tips and Maxillary Sinus Floor Using CBCT (Indian Journal of Public Health Research & Development, 2020)
Introduction: Maxillary Sinus is a triangular-shaped paranasal sinus located close to the nose and maxillaryposterior teeth. It the largest of the four paranasal sinuses and is responsible for the resonance of voiceand also in the dissipation of any unwanted forces preventing injury to maxillofacial bones. Overtimepneumatization of the maxillary sinus takes where age is a significant factor. Tooth loss may also lead toloss of bone, which in turn causes reduced bone density and insufficient bone quantity and quality for theplacement of implants.Materials and Method: CBCT scans were gathered and analyzed to establish a relationship betweenthe maxillary posterior root tips and the sinus floor. We had collected 30 CBCTs the Department of OralMedicine & Radiology, Saveetha dental college, Chennai. The distances of the root tip of the maxillary firstand second molar to the sinus floor was measured. Statistical analysis was done on the collected data.Results: Mean and standard deviations of the distance of each root tip of maxillary first and second molarfrom the maxillary sinus floor were obtained. No significant statistical difference was found between therespective roots of maxillary first and second molars.Conclusion: Knowledge regarding the relationship between posterior root tips of the maxilla and the sinusis needed to prevent any unwanted complications during dental procedures.
Keywords: CBCT, maxillary sinus, maxillary molar